Understanding Twitter Hashtags from Latent Themes Using Biterm Topic Model - Bhat, Muzafar R.; Bashir, Burhan; Kundroo, Majid A.; Ahanger, Naffi A. (Recent Patents on Engineering, 2020)
Social media, in general, and Twitter, in particular, provide a space for discourses, contemporary narratives besides a discussion about few specific social issues. People respond to these events by writing short text messages. Background: Hashtag “#” , a specific way to respond to a given raised discourse, narrative or any contemporary issue is usual to social media. Netizens write a short message as their opinion about any given issue represented using a given Hashtag. These small messages generally tend to have a latent topic (theme) as one’s opinion about it. Objective: This research is aimed to extract, represent and understand those hidden themes. Method: Biterm Topic Model (BTM) has been used in this study given its ability to deal with the short messages unlike Latent Dirichlet Allocation that expects a document to have a significant length. Results: Twitter Hashtag #M comments. Data has been modelled with ten (10) topic. Conclusion: The experimental results show that the proposed approach to understand the twittter hashtages from latent themes using biterm topic modelling method is very effective as compared to other methods.
Keywords: twitter analysis